Transforme em produto 1 + sen16°
Soluções para a tarefa
Respondido por
1
Por Prostaférese temos:
![sen(90) + sen(16) = 2*sen( \frac{90+16}{2}) *cos \frac{90-16}{2} )
sen(90) + sen(16) = 2*sen( \frac{90+16}{2}) *cos \frac{90-16}{2} )](https://tex.z-dn.net/?f=sen%2890%29+%2B+sen%2816%29+%3D+2%2Asen%28+%5Cfrac%7B90%2B16%7D%7B2%7D%29+%2Acos+%5Cfrac%7B90-16%7D%7B2%7D+%29%0A)
![sen(90) + sen(16)= 2*sen(53)*cos(37) sen(90) + sen(16)= 2*sen(53)*cos(37)](https://tex.z-dn.net/?f=sen%2890%29+%2B+sen%2816%29%3D+2%2Asen%2853%29%2Acos%2837%29)
Respondido por
1
Perguntas interessantes
Ed. Física,
11 meses atrás
Sociologia,
11 meses atrás
Matemática,
11 meses atrás
Psicologia,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás